Electrokinetic behavior of membrane zeta potential during the filtration of colloidal suspensions - Chun, MS; Cho, HI; Song, IK (ELSEVIER SCIENCE BV, 2002)
A study of the membrane zeta potential determined by the streaming potential was made to investigate the electrokinetic characterization as well as the monitoring for cake deposition on the surfaces of a filtration membrane. The membrane zeta potential related to the surface charge characteristics was determined for both flat-plate and hollow-fiber cases. In this study, we showed successfully that changes in membrane zeta potential could be used to investigate the behavior of cake deposition and fouling during the filtration of colloids. With the simultaneous monitoring for fully retentive membranes, it is found that both the permeate flux and the membrane zeta potential are decreased as the latex concentration increases. Since the development of cake layer is dependent on axial positions in the hollow-fiber membrane, the difference of zeta potential with respect to inlet and outlet positions has been observed.
Keywords: ULTRAFILTRATION MEMBRANES